2020
DOI: 10.1038/s41598-020-76053-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological changes in Lentilactobacillus hilgardii cells after cold plasma treatment

Abstract: Atmospheric cold plasma (ACP) inactivation of Lentilactobacillus hilgardii was investigated. Bacteria were exposed to ACP dielectric barrier discharge with helium and oxygen as working gases for 5, 10, and 15 min. The innovative approach in our work for evaluation of bacterial survival was the use in addition to the classical plate culture method also flow cytometry which allowed the cells to be sorted and revealed different physiological states after the plasma treatment. Results showed total inhibition of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…In this study, DNA and protein leakage were observed, particularly with prolonged cold plasma treatment of 30 and 60 min, indicating the effectiveness of cold plasma in causing cell lysis. Similar findings have been observed in cold plasma treatment of E. coli [43], Pseudomonas aeruginosa [44], and Lentilactobacillus hilgardii [45]. However, the treatment duration required for the detection of DNA and protein is longer for Gram-positive bacteria, such as S. aureus, possibly due to the thicker cell wall.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, DNA and protein leakage were observed, particularly with prolonged cold plasma treatment of 30 and 60 min, indicating the effectiveness of cold plasma in causing cell lysis. Similar findings have been observed in cold plasma treatment of E. coli [43], Pseudomonas aeruginosa [44], and Lentilactobacillus hilgardii [45]. However, the treatment duration required for the detection of DNA and protein is longer for Gram-positive bacteria, such as S. aureus, possibly due to the thicker cell wall.…”
Section: Discussionsupporting
confidence: 81%
“…The inactivating effect of cold plasma on microorganisms has already been well-documented by numerous authors. Both its direct effect on microbial cells [ 39 , 40 ] and its contribution to the microbiological safety of food products have been analyzed [ 41 , 42 , 43 ]. The findings available in the literature correspond with ours and indicate that the effectiveness of cold plasma treatment depends on the numerous parameters of the process as well as the food matrix that is subjected to the preservation process.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, plasma treatment mainly changes cell structures (pore formation and cell break) and cell growth. This structural change can be explained by the oxygen and nitrogen species induced by the plasma, promoting the oxidation of lipids and proteins of the cell membrane and causing various changes in cellular characteristics [31]. Interestingly, the SPR20 mutant had similar morphology and cell growth compared to its wild-type cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Gram-positive bacteria were more resistant to plasma than Gram-negative cells and showed no morphological changes after plasma treatment. Gram-positive species lacked an outer membrane but had a thicker murein layer, giving them higher strength and rigidity [31,35].…”
Section: Discussionmentioning
confidence: 99%